Rancang Bangun Aplikasi Web Pojok Literasi Statistik Sebagai Media Litarasi Statistik Di BPS Provinsi Kepulauan Bangka Belitung - Muhammad Hilal Ramadhan; Yang Agita Rindri; Vivin Mahat Putri (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The high number of students or university students as users of statistical data recorded by the Central Statistics Agency (BPS) is not matched by adequate understanding. These data are widely processed and used as a basis for research. Although data information is widely available, many people still cannot understand and utilize the data effectively. In today's digital era, it is imperative for BPS to undergo digital transformation, especially in terms of disseminating statistical products to remain relevant to the times. The purpose of this study is to design and develop a digital innovation in the form of a website-based statistical literacy media application to improve statistical literacy and the dissemination of statistical products. The methods in this research consist of five stages, namely collection and analysis of requirements, prototyping, prototyping evaluation, coding, testing, and system evaluation. The results of the research in the form of system testing using blackbox testing show that the application with main features such as educational content, interactive tools, monthly quizzes and challenges, as well as internship and research programs for students is running and functioning as expected.